Analysis of heavy metal characteristics and health risks of edible mushrooms in the mid-western region of China - Guofu Qin; Jia Liu; Keting Zou; Fengrui He; Yongbo Li; Ruixiao Liu; Pan Zhang; Guipeng Zhao; Ting Wang; Baozhong Chen (Scientific Reports)
Abstract This study determined the content of metal elements (As, Cd, Cr, Hg, Pb) in 9 edible mushrooms using ICP-MS, and evaluated the harm of long-term consumption of edible mushrooms to human health. The results showed that the concentrations of metal elements decreased in the order of Cd > As > Cr > Pb > Hg in edible mushrooms. The concentrations of Cd, As, Pb, and Hg were 22.95%, 8.20%, 1.64%, and 3.28% higher, respectively, than the maximum standards in China, whereas Cr did not exceed the limit. The detection rate of metal elements in Morchella esculenta (L.) Pers (M. esculenta), and Agaricus blazei Murill (A. blazei) were relatively high. The results of single factor evaluation and target hazard coefficient (THQ, HI) indicated that Dictyophora indusiata (Vent.ex Pers) Fisch (D. indusiata), A. blazei and M. esculenta were the main sources of risk. In addition, the HI values in ascending order were: Pb (0.43) < Cr (0.68) < Hg (0.92) < Cd (7.21) < As (14.02), indicating that Cd and As were the primary sources of health risks in edible mushrooms. To ensure food safety, it is recommended to strengthen the supervision of edible mushrooms, make reasonable choices, and reduce exposure levels of heavy metal pollution.